2019
DOI: 10.1038/s41598-019-50858-x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape determinants of density of blacklegged ticks, vectors of Lyme disease, at the northern edge of their distribution in Canada

Abstract: In eastern North America, including Canada, Lyme disease is caused by Borrelia burgdorferi sensu stricto and transmitted to humans by the blacklegged tick, Ixodes scapularis. The last decade has seen a growing incidence of Lyme disease in Canada, following the northward range expansion of I. scapularis tick populations from endemic areas in eastern United States. This may be attributable to movement of the many hosts that they parasitize, including songbirds, deer and small mammals. In this study, we wanted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 48 publications
4
27
1
Order By: Relevance
“…Recent studies have also focused on microclimate or microhabitat to identify I. scapularis distributions at a local scale, and have found significant associations between nymphal and adult tick densities with forest type, forest understory, dominant tree type, depth of litter layer, distance from trails, type of trails, and distance to roads, which support our findings for the dominance of forests in I. scapularis habitat suitability [15,21,22,57]. A local ecological niche model for I. scapularis in the city of Ottawa also found that distance to forests and treed land were among the strongest variables predicting the distribution of blacklegged ticks [24].…”
Section: Plos Onesupporting
confidence: 88%
See 4 more Smart Citations
“…Recent studies have also focused on microclimate or microhabitat to identify I. scapularis distributions at a local scale, and have found significant associations between nymphal and adult tick densities with forest type, forest understory, dominant tree type, depth of litter layer, distance from trails, type of trails, and distance to roads, which support our findings for the dominance of forests in I. scapularis habitat suitability [15,21,22,57]. A local ecological niche model for I. scapularis in the city of Ottawa also found that distance to forests and treed land were among the strongest variables predicting the distribution of blacklegged ticks [24].…”
Section: Plos Onesupporting
confidence: 88%
“…Deciduous forests have been shown to be most favourable for I. scapularis establishment in other studies in North America, while coniferous forests were least favourable for ticks [58,59]. However, in our model distance to both types of forest were found to be important for I. scapularis habitat, which may reflect the importance of cedar and maple forests for tick density [22]. This is also likely due to the behaviour of white-tailed deer, the main reproductive host for I. scapularis, which frequent forest edges that are dominated by coniferous trees such as white cedar, eastern hemlock, and white pines [20,60].…”
Section: Plos Onecontrasting
confidence: 58%
See 3 more Smart Citations